PDGFR-β Plays a Key Role in the Ectopic Migration of Neuroblasts in Cerebral Stroke. (4th October 2015) - Sato, Hikari; Ishii, Yoko; Yamamoto, Seiji; Azuma, Erika; Takahashi, Yoriko; Hamashima, Takeru; Umezawa, Akihiro; Mori, Hisashi; Kuroda, Satoshi; Endo, Shunro; Sasahara, Masakiyo
Abstract: The neuroprotective agents and induction of endogenous neurogenesis remain to be the urgent issues to be established for the care of cerebral stroke. Platelet-derived growth factor receptor beta (PDGFR-β) is mainly expressed in neural stem/progenitor cells (NSPCs), neurons and vascular pericytes of the brain; however, the role in pathological neurogenesis remains elusive. To this end, we examined the role of PDGFR-β in the migration and proliferation of NSPCs after stroke. A transient middle cerebral-arterial occlusion (MCAO) was introduced into the mice with conditional Pdgfrb -gene inactivation, including N-PRβ-KO mice where the Pdgfrb- gene was mostly inactivated in the brain except that in vascular pericytes, and E-PRβ-KO mice with tamoxifen-induced systemic Pdgfrb -gene inactivation. The migration of the DCX + neuroblasts from the subventricular zone toward the ischemic core was highly increased in N-PRβ-KO, but not in E-PRβ-KO as compared to Pdgfrb -gene preserving control mice. We showed that CXCL12, a potent chemoattractant for CXCR4-expressing NSPCs, was upregulated in the ischemic lesion of N-PRβ-KO mice. Furthermore, integrin α3 intrinsically expressed in NSPCs that critically mediates extracellular matrix-dependent migration, was upregulated in N-PRβ-KO after MCAO. NSPCs isolated from N-PRβ-KO rapidly migrated on the surface coated with collagen type IV or fibronectin that are abundant in vascular niche and ischemic core. PDGFR-β was suggested to be critically involved in pathological neurogenesis through the regulation of lesion-derived chemoattractant as well as intrinsic signal of NSPCs, and we believe that a coordinated regulation of these molecular events may be able to improve neurogenesis in injured brain for further functional recovery.